ANALYSIS OF TEACHER COMPETENCE IN USING DIGITAL LEARNING MEDIA - Ricky Ekaristy Purwadi; Siti Chadijah; Asep Suhana (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2024)
This study aims to analyze teacher competence in the use of digital learning media, which is increasingly relevant in the era of information technology. This competence includes the ability of teachers to select, manage, and optimize digital media to support the teaching and learning process. The study used a qualitative descriptive method with data collection through interviews, observations, and questionnaires to teachers in several schools. The results of the analysis show that most teachers have a basic understanding of digital media but still face challenges in using it optimally, such as limited technical knowledge, access to devices, and lack of special training. Supporting factors, such as the availability of infrastructure and support from the school, also affect the ability of teachers to utilize digital learning media. Recommendations from this study include the need for ongoing training and improved facilities so that teachers are better prepared to integrate technology into the learning process. This study is expected to provide insight for education policy makers to improve the quality of teacher competence in the digital era.